2000
DOI: 10.1103/physreve.62.893
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic reconstruction of sandstones

Abstract: A simulated annealing algorithm is employed to generate a stochastic model for a Berea sandstone and a Fontainebleau sandstone, with each a prescribed two-point probability function, lineal-path function, and "pore size" distribution function, respectively. We find that the temperature decrease of the annealing has to be rather quick to yield isotropic and percolating configurations. A comparison of simple morphological quantities indicates good agreement between the reconstructions and the original sandstones… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
111
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(119 citation statements)
references
References 24 publications
3
111
0
Order By: Relevance
“…This reconstruction problem leads to anisotropic microstructures, which is in contrast to other such works in literature that use a single reference (2D) image and make assumptions of http://www.immijournal.com/content/3/1/19 microstructural isotropy, i.e., slices in every direction look similar to a single input image [1]. The most popular among these methods involves matching statistical features like two-point correlation functions of a single planar image to a random 3D image using optimization procedures like simulated annealing [2,3]. Extension of these methods to achieve anisotropic microstructures has been proposed in the past using directionally dependent statistical features [4].…”
Section: Introductionmentioning
confidence: 99%
“…This reconstruction problem leads to anisotropic microstructures, which is in contrast to other such works in literature that use a single reference (2D) image and make assumptions of http://www.immijournal.com/content/3/1/19 microstructural isotropy, i.e., slices in every direction look similar to a single input image [1]. The most popular among these methods involves matching statistical features like two-point correlation functions of a single planar image to a random 3D image using optimization procedures like simulated annealing [2,3]. Extension of these methods to achieve anisotropic microstructures has been proposed in the past using directionally dependent statistical features [4].…”
Section: Introductionmentioning
confidence: 99%
“…In the past decades, several approaches have been proposed to numerically reconstruct the microstructure of a natural porous medium [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Among these approaches is the commonly used stochastic rock reconstruction [1-3, 6, 8, 11, 15, 18-20], which relies on matching statistical properties of a three-dimensional model to those of a real rock microstructure.…”
Section: Introductionmentioning
confidence: 99%
“…However, reconstructions of experimental data sets based on these characterisations have been shown to give a poor representation of the connectivity of the systems [26]. Functions that may provide more complete information about connectivity [16] are unfortunately too complex to incorporate into reconstruction schemes [26].…”
Section: Spatial Structures: Experimental Data and Stochastic Modelsmentioning
confidence: 99%
“…Of course, one can derive more complex model systems which incorporate other two-point correlation information (e.g., chord distribution functions [47,53]. Recent work [26] has shown that these measures give a poor representation of connectivity. Preliminary results on Minkowski functionals of these more complex models indicate that this is reflected in a poor match to the v 2 measure.…”
Section: Characteristics Of a Sandstone Samplementioning
confidence: 99%